Managerial Ownership in a Private Firm Framework - Gao, Chao; Johnston, Mitchell (The Review of Corporate Finance Studies, 2026)
We study the relationship between managerial ownership and firm performance in a unique private firm setting. The simplicity of the ownership structure and nature of our sample firms help isolate the incentive-aligning effect of managerial ownership from the influence of other effects. We find that managerial ownership is positively associated with firm performance. This positive association is concave but not reversed as ownership increases, indicating a diminishing effect of ownership on performance. We use unique features of the data to further mitigate endogeneity concerns. Our findings support managerial ownership as an effective incentive-aligning tool in the absence of managerial entrenchment.